2021
DOI: 10.1364/oe.413660
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the phase change process in a GST-loaded silicon waveguide and MMI

Abstract: In the past decades, silicon photonic integrated circuits (PICs) have been considered as a promising approach to solve the bandwidth bottleneck in optical communications and interconnections. Despite significant advances, large-scale PICs still face a series of technical challenges, such as footprint, power consumption, and routing state storage, resulting from the active tuning methods used to control the optical waves. These challenges can be partially addressed by combining chalcogenide phase change materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…On the topic of comparison between electrical switching and optical switching in GST-based silicon photonic switches, Zhang concluded that, for the amorphization process, optical switching is advantageous in terms of speed and energy efficiency. However, as alluded to earlier, for large-scale integration purposes, electrical switching is still advantageous as it does not require a complex routing circuit for the photonic circuit [101].…”
Section: Optical Switchingmentioning
confidence: 99%
“…On the topic of comparison between electrical switching and optical switching in GST-based silicon photonic switches, Zhang concluded that, for the amorphization process, optical switching is advantageous in terms of speed and energy efficiency. However, as alluded to earlier, for large-scale integration purposes, electrical switching is still advantageous as it does not require a complex routing circuit for the photonic circuit [101].…”
Section: Optical Switchingmentioning
confidence: 99%
“… a The energy densities and switching speeds were found to strongly depend on the design and switching mechanism (optical or electrical), as well as on the preparation methods and deposition conditions, refs . The values reported here should therefore not be seen as fundamental ones, but rather as state-of-the-art metrics that we collected from different works that we find representative of the different values reported in the literature. …”
Section: From Current Key Enabling Technologies To Tunable Metasurfacesmentioning
confidence: 69%
“…For q = −5.6, the narrowband absorption with absorption coefficient A = 0.94 (reflection coefficient R = 0.02) and prominent Q = 190 promises a high Q switching (Figure 4b). To implement the switching in the modern photonic platform, one can integrate thermal control components 35 or optical/electrical excitation optical circuits 36 to the Fano resonator, which are common routes to modulate GST phase transition in silicon photonics. 37 Proper optical imaging setup helps to visualize the effect of optical switching from high Q absorption to high Q reflection.…”
Section: ■ Design and Resultsmentioning
confidence: 99%